Design for the First Narrowband Filter for the Dark Energy Camera: Optimizing the LAGER Survey for z ∼ 7 Galaxies. (3rd June 2019) - Zheng, Zhen-Ya; Rhoads, James E.; Wang, Jun-Xian; Malhotra, Sangeeta; Walker, Alistair; Mooney, Thomas; Jiang, Chunyan; Hu, Weida; Hibon, Pascale; Jiang, Linhua; Infante, Leopoldo; Barrientos, L. Felipe; et al.
Abstract: We present the design for the first narrowband filter, NB964, for the Dark Energy Camera (DECam), which is operated on the 4-m Blanco Telescope at the Cerro Tololo Inter-American Observatory. The NB964 filter profile is essentially defined by maximizing the power of searching for Lyman-alpha emitting galaxies (LAEs) in the epoch of reionization, with the consideration of the night sky background in the near-infrared and the DECam quantum efficiency. The NB964 filter was manufactured by Materion in 2015. It has a central wavelength of 964.2 nm and a full width at half maximum (FWHM) of 9.2 nm. An NB964 survey named Lyman Alpha Galaxies in the Epoch of Reionization (LAGER) has been ongoing since December 2015. Here, we report results of lab tests, on-site tests, and observations with the NB964 filter. The excellent performances of this filter ensure that the LAGER project is able to detect LAEs at z  ∼ 7 with a high efficiency.